Balancing traction resources based on fluctuations in train speeds and required traction reserves - N. V. Kornienko; M. I. Mekhedov; A. G. Kotenko (Вестник Научно-исследовательского института железнодорожного транспорта)
Introduction. The rational operation of the locomotive fleet is based on coordination of the locomotive turnover schedule with the train traffic schedule that assume unconditional fulfillment of standard transportation jobs and no less strict compliance with technical and technological standards for locomotive and train operations at locomotive turnover and re-coupling stations. Coordination is intended to set up balance of locomotives at traction interchange points. However, in the course of transportation, the intra-day dislocation of the operating fleet reaches significant unevenness and leads to imbalance. This requires a system for dispatching traction resources to their turnover and recoupling stations which will help to preserve traction balance at the interchange points to compensate for uneven intraday dislocation of the operating fleet, rationalise the locomotive fleet operations, and improve line capacity.Materials and methods. The balance of traction resources at locomotive turnover and re-coupling stations in intra-day intervals is achieved by interval regulation of traction resources.Results. The paper proposes an approach to establishing a balance of traction resources at current interlocking stations as the simplest type of turnover and recoupling stations (as a rule, they do not have additional adjacencies, using a one-to-one traction exchange). The approach applies the correlation between fluctuations in train traffic speeds and the amount of required traction reserves within daily three-hour intervals.Discussion and conclusion. This approach helps to improve the traction resource balancing technology at the current junction stations, and create a basis for building a mechanism for dispatching regulation reserves.